Life comfort estimation after surgical treatment of urinary incontinence - Jędrzejczyk, Sławomir; Kłosiński, Witold; Lau, Katarzyna; Wieczorek, Marek; Rutkowska, Beata; Izdebski, Bartosz (Menopause Review/Przegląd Menopauzalny, 2008)
Background: Urine incontinence is defined as involuntary leakage of urine from urethra. This is a serious medical problem at menopausal and postmenpausal age. The aim of the study was to compare the quality of life after TOT procedure. Material and methods: In our study we included 28 patients aged between 47-60 years old. All patients were operated in Dept. of One Day Gyneacological Surgery Clinic of Medical University of Lodz and answered to our questionnaire before and 4 months after operation. Results: In all group the frequency of miction was average 9,0 times a day before operation and 6,1 after. The cure rate of TOT procedures increase quality of life of all patients. Conclusions: Transobturator tape procedure is very effective surgical treatement which provides to better miction control and reduced frequency of miction. Four months after operation we did not observe additional side-effects connected with urine incontinence.